Layer-by-layer heparinization of decellularized liver matrices to reduce thrombogenicity of tissue engineered grafts - Bruinsma, Bote G (J Clin Transl Res, 2015)
BACKGROUND: Tissue–engineered liver grafts may offer a viable alternative to orthotopic liver transplantation and help overcome the donor organ shortage. Decellularized liver matrices (DLM) have a preserved vasculature and sustain hepatocellular function in culture, but graft survival after transplantation remains limited due to thrombogenicity of the matrix. AIM: To evaluate the effect of heparin immobilization on DLM thrombogenicity. METHODS: Heparin was immobilized on DLMs by means of layer-by-layer deposition. Grafts with 4 or 8 bilayers and 2 or 4 g/L of heparin were recellularized with primary rat hepatocytes and maintained in culture for 5 days. Hemocompatibility of the graft was assessed by ex vivo diluted whole-blood perfusion and heterotopic transplantation. RESULTS: Heparin was deposited throughout the matrix and the heparin content in the graft was higher with increasing number of bilayers and concentration of heparin. Recellularization and in vitro albumin and urea production were unaffected by heparinization. Resistance to blood flow during ex vivo perfusion was lower with increased heparinization and, macroscopically, no clots were visible in grafts with 8 bilayers. Following transplantation, flow through the graft was limited in all groups. Histological evidence of thrombosis was lower in heparinized DLMs, but transplantation of DLM grafts was not improved. CONCLUSIONS: Layer-by-layer deposition of heparin on a DLM is an effective method of immobilizing heparin throughout the graft and does not impede recellularization or hepatocellular function in vitro. Thrombogenicity during ex vivo blood perfusion was reduced in heparinized grafts and optimal with 8 bilayers, but transplantation remained unsuccessful with this method. RELEVANCE FOR PATIENTS: Tissue engineered liver grafts may offer a viable solution to dramatic shortages in donor organs